Diagnóstico de Aspectos Socioambientais da Microbacia do Açude do Arriba - Forquilha - CE - Aragão, Deborah de Andrade (2011)
The circunstances provoked by droughts on the semi-arid of the northeastern region of Brazil, assumed along the history, a unavoidable character that led to the adoption of politics related to the construction of hydric reservoirs as an attempt to mitigate the effects of drought. However, the construction of a great number of reservoirs, done in a random way, without observing its framing to the conditions of the hydric dynamics as well as its yours support capacity, allied to an ocupation, motivated by the offer of water, ended up inserting itself in the context of socioenvironmental problematic. The analysis of the decision process in allocating different uses for water involves several dificulties which characterizes the present context. Among the most important are the necessary interdisciplinar approach to the subject matter, the subjectivity of the agents involved in the process of water management, the randomness of the hydrologic events, the uncertainty of the economic, social and environmental processes, the difficulties in measuring such variables as social well-being and environmental protection and others as cultural and aesthetics, besides the traditional problem of measuring economic efficiency. This dissertation presents, examines and compare some techniques of socioenvironmental analysis as important support tools for decision-making in water management. Therefore, the integration of hydric resources management through the institution of hydric basins as an unit of management should consider as prioritary manner, the question of damming as concern to the northeastern hydric resources, in special, the ones of small size, that support directly the local communities and which are more seriously affected by the degradation generated by antropic actions as well as inadequate use.